A revision and redescription of the rock gecko Cnemaspis siamensis (Taylor 1925) (Squamata: Gekkonidae) from Peninsular Thailand with descriptions of seven new species - Grismer, L. Lee; Sumontha, Montri; Cota, Michael; Grismer, Jesse L.; Wood, Jr., Perry L.; Pauwels, Olivier S. G.; Kunya, Kirati (Zootaxa, 2010)
A taxonomic revision of Cnemaspis siamensis (Smith 1925) revealed it to be a complex composed of four species: C. siamensis (Smith 1925) which occurs on Ko Tao Island, Surat Thani Province and on the peninsula ranges from Khao Mod, Surat Thani Province in the south, northward east of the Tenasserim Mountains to Kaeng Krachan National Park, Phetchaburi Province; C. chanardi sp. nov. ranging from Tai Rom Yen National Park, Surat Thani Province in the north, southward through the western foothills of the Nakhon Si Thammarat and Sankalakhiri Mountains to Phuphaphet Cave, Satun Province and westward to Khlong Thom District, Krabi Province; C. vandeventeri sp. nov. ranging from Kapur District, Ranong Province southward to at least Khlong Had Sompen, District, Ranong Province west of the Tenasserim and Phuket Mountains and possibly all the way to Phuket Island; and C. kamolnorranathi sp. nov. restricted to the northwestern section of the Itshmus of Kra, ranging from Tham Khao Sonk, Thachana District, Surat Thani Province southward to Tai Rom Yen National Park, Surat Thani Province. These species are easily separated from one another on the basis of their unique combination of having or lacking precloacal pores, dark gular markings, a series of lightly colored bars on the flanks, and a lightly colored, prescapular crescent as well as other aspects of squamation. Four additional new species from western and southern Thailand are also described: C. huaseesom sp. nov. from Sai Yok National Park, Kanchanaburi Province; C. punctatonuchalis sp. nov. from Thap Sakae District, Prachuap Khiri Khan Province; C. narathiwatensis sp. nov. ranging from Waeng District, Narathiwat Province south to Bang Lang, Yala Province; and C. niyomwanae sp. nov. from Thum Khao Ting, Palean District, Trang Province, Thailand. These species are differentiated from each other and all other Cnemaspis on the basis of their unique combinations of color pattern and squamation characters. This brings the total number of species of Cnemaspis in Thailand from five to 12 and continues to illustrate that the unrealized diversity in this group is a function of unfocused collecting efforts coupled with poor taxonomy.